Характеристики мощного шестимпульсного мостового неуправляемого выпрямителя с емкостным фильтром - Жемеров, Г.Г.; Ковальчук, О.И. (Електротехніка і електромеханіка, 2011)
The article deals with modes of operation and characteristics or the high-power three-phase full-bridge diode rectifier with the dc-side capacitance filter.